Outcome and Management of Occipitofrontal Contrecoup Head Injury - Srivastava, Syamantak; Kannan, Ganapathyvel; Srisaravanan, J.; Rajaraajan, K. (Asian Journal of Neurosurgery, 2024)
Contrecoup brain injury refers to the classical opposite of the primary impact. Tamil Nadu has the highest rate of road traffic accident in India. Madurai has peak mortality due to accidents in India. Previous studies done on contrecoup head injury had shown patterns of injuries and mechanism of injury. Outcome and management of only occipitofrontal contrecoup head injury has been taken in this study. Mortality in this specific group is very high. Seventy-six patients of this specific head injury were admitted at Government Rajaji Hospital, Madurai. Patients were assessed for Glasgow coma scale (GCS), age, sex, progression of volume, mortality, traumatic brain injury-induced coagulopathy, and pillion rider outcome. Fourteen patients were surgically treated by decompressive craniectomy. Conservative management was done by antiepileptic and antiedema measures. Mostly affected were males (n = 54) followed by females (n = 22). GCS on admission mean value 9. In our study, mortality was 32% with sudden death of three patients due to hypothalamic compression. Hospital stay of the patient was significantly increased with progression of lesion with mean 9 days and p-value less than 0.01. Pillion riders (n = 18) were also affected in our study. Traumatic brain injury-induced coagulopathy (n = 12) was also detected, which was treated by injection tranexamic acid and injection vitamin K, thereby not leading to any death due to coagulopathy with significant p-value less than 0.01. We recommend helmet for both main and pillion rider with strict speeding regulations.
Keywords: contrecoup head injury; frontal hemorrhagic contusion; mortality; occipital bone fracture; pillion rider; traumatic brain injury-induced coagulopathy; road traffic accidents